2019
DOI: 10.3389/fpls.2019.01236
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetylation Dynamics Integrates Metabolic Activity to Regulate Plant Response to Stress

Abstract: Histone lysine acetylation is an essential chromatin modification for epigenetic regulation of gene expression during plant response to stress. On the other hand, enzymes involved in histone acetylation homeostasis require primary metabolites as substrates or cofactors whose levels are greatly influenced by stress and growth conditions in plants. In addition, histone lysine acylation that requires similar enzymes for deposition and removal as histone acetylation has been recently characterized in plant. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 92 publications
0
72
1
2
Order By: Relevance
“…Histone and chromatin modifications are important epigenetic mechanisms controlling gene expression underlying growth and stress responses (Chinnusamy and Zhu, 2009; Weng et al, 2014; Lee et al, 2017). There are numerous reports which suggested the role of histone acetylation and methylation (specifically H3K4 di- and tri-methylation) in gene transcriptional activation underlying stress responses (Saleh et al, 2008; Hu et al, 2015; Hu et al, 2019; Ueda and Seki, 2020). Recently, Chen et al, 2019 showed that p300/CREB HISTONE ACETYLTRANSFERASE 1 (HAC1) in association with WRKY18/53 transcription factors regulate sugar responsive gene expression by modulation of histone acetylation (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Histone and chromatin modifications are important epigenetic mechanisms controlling gene expression underlying growth and stress responses (Chinnusamy and Zhu, 2009; Weng et al, 2014; Lee et al, 2017). There are numerous reports which suggested the role of histone acetylation and methylation (specifically H3K4 di- and tri-methylation) in gene transcriptional activation underlying stress responses (Saleh et al, 2008; Hu et al, 2015; Hu et al, 2019; Ueda and Seki, 2020). Recently, Chen et al, 2019 showed that p300/CREB HISTONE ACETYLTRANSFERASE 1 (HAC1) in association with WRKY18/53 transcription factors regulate sugar responsive gene expression by modulation of histone acetylation (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In plants, the activities of sirtuin HDACs are dependent on the NAD + level and NAD + /NADH ratio [21]. Thus, oxidative stress alters the redox status of NAD + , and may further imprint on HDAC activity.…”
Section: Redox Affecting Chromatin Remodelers and Other Chromatin-assmentioning
confidence: 99%
“…In recent years, many review papers covering the roles and regulatory mechanisms of epigenetic modifications have been published. The relationship between redox metabolites and some epigenetic modifications has also been discussed [8, [10][11][12][19][20][21][22]. However, the functions and mechanisms of redox mediators modulating the epigenetic modifications are not comprehensively summarized.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the affinity of the histone tail for the DNA and contributes to release the interaction between histones and DNA, and to open the chromatin (Barnes et al, 2019). Due to its great impact on a myriad of cellular and developmental processes, the antagonistic action of two classes of enzymes, histone deacetylases (HDACs), and histone acetyltransferases (HATs), has been the subject of a growing number of studies (Liu et al, 2014;Hu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%